TAHSIN AL-ADA’ AL-TA’LIMI LI MUDARRISI AL-LUGAH AL-ARABIYAH LI GAIRI AL-NATHIQINA BIHA - Sudi Yahya Husein; H. Djuaini (Universitas Islam Negeri Mataram, 2019)
This articleaims to answer the following questions. (1)What isthe educational performance in teaching Arabic to non-native speakers? (2)What is the scope of educational performance in teaching Arabic to nonnativespeakers? (3) What requires educational performance in teachingArabic to non-native speakers? To reach the objectives of the interview, theresearcher used the descriptive analytical method, starting from gatheringinformation and data about the concept of the educational process and itselements, then analyzing and arranging them according to the requirementsand the research hypothesis. After presenting and analyzing, the researcherobtained the results of this research as follows: (1) It defines the concept ofeducational performance, but it revolves around three things, namely: theeffort and the teacher performing the system, the rules, and the scope ofthe performance work. (2) The scope of educational performance is all theperformance of the teacher in the educational field, from mastery and masteryof teaching methods, teaching methods and educational material, knowledgeof individual differences for learners, classroom management, calendar andmethods of performance. (3) That a well-performing teacher is the one whoperformed his educational tasks according to educational standards, who isable in education and has the ability to awaken the attention of learners andraise their motivation towards learning and achieving educational goals, andhas a positive impact personally and professionally for his children learners.